Role of Hippo Signaling in Cancer Stem Cells. Issue 3 (March 2014) - Hao, Jin; Zhang, Yueling; Jing, Dian; Li, Yu; Li, Juan; Zhao, Zhihe
Abstract Cancer stem cells (CSCs) have been proposed and evidenced as the initiator of tumor formation and the seeds of metastases. Thereby, the molecular mechanisms regarding modulation of CSCs have been widely explored, aimed to improve treatment for cancer patients. Recent progress has highlighted the effects of Hippo signaling in tumorigenesis and cancer development, including its crucial role in CSC regulation. Although the kernel Hippo signaling cascade has been well studied, its upstream inputs and downstream transcriptional regulation still remain elusive. In this review, we summarize the current understanding of the mechanism and regulatory function of Hippo signaling in CSCs, with emphasis on its possible roles in regulation of CSC self‐renewal, differentiation and tumorigenesis. J. Cell. Physiol. 229: 266–270, 2014. © 2013 Wiley Periodicals, Inc.